Whole Genome Sequencing of a Canadian Bovine Gammaherpesvirus 4 Strain and the Possible Link between the Viral Infection and Respiratory and Reproductive Clinical Manifestations in Dairy Cattle - Gagnon, Carl A.; Traesel, Carolina Kist; Music, Nedzad; Laroche, Jérôme; Tison, Nicolas; Auger, Jean-Philippe; Music, Sanela; Provost, Chantale; Bellehumeur, Christian; Abrahamyan, Levon; Carman, Susy; DesCôteaux, Luc; et al. (Frontiers in Veterinary Science, 2017)
Bovine gammaherpesvirus 4 (BoHV-4) is a herpesvirus widespread in cattle populations, and with no clear disease association. Its genome contains a long unique coding region (LUR) flanked by polyrepetitive DNA. In 2009, a BoHV-4 strain was isolated (FMV09-1180503: BoHV-4-FMV) from cattle with respiratory disease from Quebec, Canada, and its LUR was sequenced. Despite the overall high similarity, BoHV-4-FMV had the most divergent LUR sequence compared to the two known BoHV-4 reference strain genomes; most of the divergences were in the Bo genes and in the repeat regions. Our phylogenetic analysis based on DNA polymerase and thymidine kinase genes revealed that virus isolate was BoHV-4 gammaherpesvirus and clustered it together with European BoHV-4 strains. Because BoHV-4-FMV was isolated from animals presenting respiratory signs, we have updated the BoHV-4 Canadian cattle seroprevalence data and tried to find out whether there is a link between clinical manifestation and BoHV-4 seropositivity. An indirect immunofluorescence assay (IFA) was performed with near 200 randomized sera of dairy cattle from two Canadian provinces, Quebec (n=100) and Ontario (n=91). Quebec’s sera of selected dairy cattle herds experiencing respiratory or reproductive problems (n=75) and healthy herds (n=48) were also analyzed by IFA. BoHV-4 seroprevalence in Canadian dairy cattle was 7.9% (Quebec: 6% and Ontario: 9.9%). Among Quebec’s selected herds, diseased herds showed higher BoHV-4 seropositivity than healthy herds (P<0.05), with a significant 2.494 odds ratio of being seropositive in sick compared to healthy animals. Although there is no established direct link between BoHV-4 and specific diseases, these seroprevalence data suggest the possible involvement of BoHV-4 in dairy cattle diseases.